Leishmaniasis Tegumentaria y su repercusión clínica en la cavidad oral - Romero Rivas, Roberto (2003)
This is a study of tegumentary leishmaniasis from patiens, whom origin was andean and mountain locations. They arrived Hospital 2 de Mayo with mucosal and cutaneous lesions some of them ulcerated and not ulcerated in the oral cavity. They were identified granulomatous leishmaniasic lesions in mucosa and muscle in lips, fornix and orofarynx, Vegetative lesions were found only in hard palate.